Pacemaker Implantation in a Patient With Isolated Persistent Left Superior Vena Cava: A Novel Approach - Shayan Shahi; Soroush Nematollahi; Ali Vasheghani‐Farahani (Clinical Case Reports)
ABSTRACT Implanting pacemakers in patients with isolated persistent left superior vena cava (PLSVC) present unique challenges. Recognizing venous anomalies and adapting lead placement techniques are crucial for successful outcomes and stable pacemaker function.